Plasma extracellular vesicle microRNA profiling and the identification of a diagnostic signature for stage I lung adenocarcinoma. Issue 2 (6th December 2021) - Gao, Shugeng; Guo, Wei; Liu, Tiejun; Liang, Naixin; Ma, Qianli; Gao, Yibo; Tan, Fengwei; Xue, Qi; He, Jie
Abstract: At present, there is no effective noninvasive method for the accurate diagnosis of early‐stage lung adenocarcinoma (LUAD). This study examined the profile of plasma extracellular vesicle (EV)‐delivered microRNAs (miRNAs) in patients with invasive stage I LUAD. In this study, a total of 460 participants were enrolled, including 254 patients with LUAD, 76 patients with benign pulmonary nodules (BPNs), and 130 healthy control patients (HCs). miRNA sequencing was used to analyze the EV miRNA profile of the patient plasma samples (n = 150). A diagnostic signature (d‐signature) was identified by applying a stepwise logistic regression algorithm, and a single‐center training cohort (n = 150) was tested, followed by a multicenter validation cohort (n = 100). A d‐signature comprising four EV‐derived miRNAs (hsa‐miR‐106b‐3p, hsa‐miR‐125a‐5p, hsa‐miR‐3615, and hsa‐miR‐450b‐5p) was developed for the early detection of LUAD. The d‐signature had high precision with area under the curve (AUC) values of 0.917 and 0.902 in the training and test cohorts, respectively. Moreover, the d‐signature could recognize patients with adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) with AUC values of 0.846 and 0.92, respectively. To sum up, our study detailed the plasma EV–derived miRNA profile in early LUAD patients and developed an EV‐derived miRNA d‐signature to detect early LUAD. Abstract : This study provides the largest genome‐wide analysis of extracellular vesicle (EV) microRNA (miRNA) in plasma from early lung adenocarcinoma (LUAD) patients, suggesting the feasibility of identifying cancer biomarkers based on EV miRNA profiling. We developed an EV miRNA–based diagnostic signature (d‐signature) that showed high accuracy for the diagnosis of early LUAD based on multicentric validation. The d‐signature was able to detect adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) as readily as invasive stage I invasive adenocarcinoma (IAC).